The millipede family Striariidae Bollman, 1893: I. Introduction to the family, synonymy of Vaferaria Causey with Amplaria Chamberlin, the new subfamily Trisariinae, the new genus Trisaria, and three new species (Diplopoda, Chordeumatida, Striarioidea) - Shear, William A. (Zootaxa, 2020)
The significant taxonomic characters of the millipede family Striariidae Bollman, 1888 are discussed. The monotypic genus Vaferaria Causey, 1958 is synonymized under Amplaria Chamberlin, 1941, giving the new combination Amplaria imberbis (Loomis, 1936). The genera Striaria Bollman, 1888 and Amplaria are assigned to the subfamily Striariinae. A new subfamily, Trisariinae, is established that presently includes only Trisaria new genus, with three new species: Trisaria rex, T. olympia and T. washingtonensis. The new subfamily, genus, and species are endemic to western Washington state, USA.